THE APPLICATION OF ROTATED PRACTICE METHOD TO IMPROVE PRACTICE LEARNING ACHIEVEMENT IN VOCATIONAL SCHOOL - bambang sudarsono (VANOS Journal of Mechanical Engineering Education, 2020)
This study aims to determine: (1) the application of rotated practice method in learning the practice of automotive electrical system learning. (2) improvement of student learning achievement after the application of the rotated practice method in learning practices of automotive electrical system learning subjects. The design of this study used a classroom action research design and stopped at cycle two (II). The subject of the study was class XI of light vehicle engineering students class B with a total of 30 students. While the object of research carried out at SMK YPT Purworejo. Data collection used test. The research instrument used practicum questions which consisted of 5 job sheets. The data analysis technique used in this research was descriptive analysis. The results of the study showed that: (1) the method of rotated practice in learning the practice of learning automotive electrical systems can be applied well by students. (2) Student learning achievements in the pre cycle conducted by researchers got the final result 74.14. In the first cycle there was an increase in learning achievement to 76.48 and in the second cycle student learning achievement increased to 84.14 with 100% completeness.